2015
DOI: 10.1021/acsami.5b00758
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Amphiphilicity and Multifunctional Applications of Ionic-Liquid-Modified Carbon Quantum Dots

Abstract: During the past decade, increasing attention has been paid to photoluminescent nanocarbon materials, namely, carbon quantum dots (CQDs). It is gradually accepted that surface engineering plays a key role in regulating the properties and hence the applications of the CQDs. In this paper, we prepared highly charged CQDs through a one-pot pyrolysis with citric acid as carbon source and a room-temperature imidazolium-based ionic liquid as capping agent. The as-prepared CQDs exhibit high quantum yields up to 25.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 42 publications
9
96
0
Order By: Relevance
“…They are mainly used for fluorescence imaging and drug delivery 25 in the medical field. Many CDs manufacturing methods have been developed, including pyrolysis 26 , hydrothermal 27 , calcination 28 , microwave assisted 29 , and laser-assisted 30 . Various raw materials have been adopted for the preparation of quantum dots, including glucose 31 , garlic 32 , wool 8 , candle soot 33 , and graphite 34 .…”
Section: Discussionmentioning
confidence: 99%
“…They are mainly used for fluorescence imaging and drug delivery 25 in the medical field. Many CDs manufacturing methods have been developed, including pyrolysis 26 , hydrothermal 27 , calcination 28 , microwave assisted 29 , and laser-assisted 30 . Various raw materials have been adopted for the preparation of quantum dots, including glucose 31 , garlic 32 , wool 8 , candle soot 33 , and graphite 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The average diameter was 5.5 nm and they had a narrow size distribution ranging from 3 to 8 nm. The HR-TEM image also showed clear lattice spacing with an interfringe distance of 0.345 nm, which may be attributed to the (002) facet of the sp 2 graphitic crystal phase of graphene [29]. Most of these CDs were amorphous but a typical X-ray difvia chemical synthesis, such as chemical or thermal oxidation of suitable chemical precursors [14,15], ultrasonic treatment of alkali or acid aqueous solutions of glucose [16,17], and microwave pyrolysis of carbohydrates [18,19].…”
Section: Physiochemical Characterizationmentioning
confidence: 99%
“…2c. Noticeably stronger peaks emerged at 3406 cm −1 , which may correspond to the stretching vibrations of O-H and N-H. A variety of peaks at 1702, 1614, 1408, and 1247 cm −1 were assigned to the stretching vibrations of C=O in ketone, stretching vibrations of C=C and C=N, and bending vibrations of −OH, respectively [21,29,30]. These results indicated that the asprepared CDs possessed abundant functional groups, which is beneficial for enhancing their PL property.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…Besides, the surfactant molecule plays a special role in surface chemistry. Especially, surface active ionic liquids (SAILs) such as imidazolium-, pyrrole-based ionic liquids have attracted widespread interest for their outstanding performance in biomaterials, photoelectricity, and environmentally friendly trades, since they possess good biocompatibility, low critical micellar concentrations, wide liquid range, and high thermal stability [20,21]. Thus, the introduction of charged dye molecules or surfactants as ISA components will generate novel properties and structures of the systems and enrich the ranges and contents of ISA.…”
Section: Dye-surfactant Isa Materialsmentioning
confidence: 99%